Antioxidant Activity, Formulation, and Evaluation of Roselle Seed Oil Extract Nanoemulsions - Arpa Petchsomrit (Journal of Global Pharma Technology, 2020)
Roselle Hibiscus is a medicinal plant used in folk medicine. The parts of the flower, calyx, and bracts, are regularly used but the seed of roselle has not been used and studied for antioxidant activities. The objective of the present work was to determine the antioxidant activity of roselle seed oil extract extracted using dichloromethane maceration. The extraction then was formulated as nanoemulsions and evaluated for its physicochemical properties and stability. The oil obtained from Roselle Hibiscus seed demonstrated good antioxidant activity, according to the DPPH assays. Roselle seed oil extract nanoemulsions were developed using non-ionic surfactants and water by ultrasonic emulsification method and evaluated to achieve optimum stability. Nanoemulsions formulated using Tween 60 and Tween 80 had a relatively small droplet size ranging from 20-30 nm. After a seven-day stability test at the room temperature and a 6-cycle heating-cooling study, phase separation or creaming did not occur to the nanoemulsions formulated by Tween 60 and Tween 80. The ratio of roselle seed oil extract and Tween 60 that yielded the best physical properties for the nanoemulsions was 1% and 5%, respectively. The results indicated that nanoemulsions had nanoscale droplet size and were stable under the normal and stress storage condition.